Analysis of antibiotic resistance in active valve infective endocarditis - Krykunov, O. A.; Buryak, R. V.; Koltunova, G. B.; Spisarenko, S. P.; Pustovalova, G. O.; Khmelevsky, A. M. (Ukrainian Journal of Cardiovascular Surgery, 2017)
Current trends in the epidemiology of infective endocarditis (IE) are expansion of the pathogens spectrum and antibiotic resistance of microorganisms. The growth of pathogens antibiotic resistance has negative impact on the occurrence of complicated forms of disease and increase hospital mortality. The data were retrived from 116 patients with infective endocarditis, who passed examination and treatment in SE «Amosov National Institute of Cardio-Vascular surgery of the Academy of Medical Sciences of Ukraine» from January 2014 to December 2016. The microbiological constitutions of positive cultures revealed the prevalence of Staphylococcus spp. – 65 (56%) cases. Streptococcus spp. and Enterococcus spp. were identified in 11 (9.5%) and 27 (23.3%) cases respectively. Gram-negative pathogens and fungal microflora were identified in 10 (8.6%) and 2 (1.7%) cases respectively. Conducted study showed that among Gram-positive microorganisms in patients with infective endocarditis in 70.1% of cases oxacillin-resistant pathogens were registered. It means that for 2/3 of patients penicillin and cephalosporin drugs should not be included to the scheme of empirical antibiotic therapy. Therefore, for these patients alternative drug groups – glycopeptides, lipopeptides and linezolid - should be used. It should be borne in mind that the proportion of strains resistant to Vancomycin, Linezolid, and Gentamicin was 22.1%, 4.8% and 27.9% of cases respectively. To achieve synergy of action it is desirable to combinate bactericidal drugs (glycopeptides, lipopeptides) with Gentamicin. Resistance to Tigecycline was not found, but bacteriostaticity of this drug limits its use.